2016
DOI: 10.1186/s12917-016-0906-2
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology and associated risk factors of Toxoplasma gondii in sheep and goats in Southwestern Ethiopia

Abstract: Background T.gondii is a global zoonotic disease and is considered as the most neglected tropical disease in sub-Saharan countries. The exact seroepidemiological distribution and risk factors for the infection of food animals and humans in Ethiopia was less studied although, such studies are important. The objective of the current study was to determine the seroprevalence and potential risk factors of T. gondii infection in sheep and goats in Southwestern Ethiopia.MethodsCross sectional study was conducted fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
29
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 35 publications
15
29
4
Order By: Relevance
“…As expected, being an adult sheep was a risk factor for T. gondii seropositivity, also in the final model wherein the breed of the sheep and the location of the farm were included (Table 2). Older age has been identified as a risk factor for T. gondii seropositivity also in other studies (Dumétre et al 2006, Halos et al 2010, Lopes et al 2013a, Tegegne et al 2016, Deksne et al 2017. These results indicate that most ovine T. gondii infections are acquired postnatally.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…As expected, being an adult sheep was a risk factor for T. gondii seropositivity, also in the final model wherein the breed of the sheep and the location of the farm were included (Table 2). Older age has been identified as a risk factor for T. gondii seropositivity also in other studies (Dumétre et al 2006, Halos et al 2010, Lopes et al 2013a, Tegegne et al 2016, Deksne et al 2017. These results indicate that most ovine T. gondii infections are acquired postnatally.…”
Section: Discussionsupporting
confidence: 69%
“…The age of each sheep was rounded to full months. Age was evaluated as a dichotomous variable (lamb: <12 months vs. adult: ‡ 12 months) (Halos et al 2010, Tegegne et al 2016, Deksne et al 2017, as a continuous variable, and graphically as a categorized variable. The breeds were evaluated as dummy variables; the breeds presented by <10 sheep were categorized as 'other breed'.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…The molecular prevalence of T. gondii was estimated to be 37.65% population, and the seroprevalence was 42.47% by ELISA ( Table 2 ). The prevalence of T. gondii in goats has been reported to vary from 1.34% to 55.18% [ 1 , 2 , 4 , 11 , 12 , 29 ]. The relatively high prevalence of T. gondii in goats in Chongqing may be related to: 1) the oocysts of T. gondii excreted by infected cats that can easily develop to infective stages under the subtropical monsoon climate and humid weather in Chongqing and that are ingested by goats during grazing, and 2) the fact that most goats investigated in Chongqing were semi-housed, potentially increasing the risk of T. gondii sporulated oocyst ingestion in wild grazing conditions.…”
Section: Resultsmentioning
confidence: 99%
“…The higher prevalence in goats was in line with Barakat et al [ 6 ], who found prevalences of 55% and 44% in 306 goats and 320 sheep, respectively, from the Giza governorate; however, Ghoneim et al [ 5 ] found prevalences of 42% and near 100% in 10 goats and 61 sheep from the Faiyum governorate, but this could have been due to the very low sample size. A higher T. gondii infection in goats than in sheep may be due to differences in herding practices [ 18 ], although this requires further investigation. The observed difference may also be confounded by a different age at slaughter; unfortunately, information on the age of the sampled animals was not available.…”
Section: Discussionmentioning
confidence: 99%